ICT adoption in Cameroon SME: application of Bass diffusion model*. Issue 2 (3rd April 2017) - Ntwoku, Habib; Negash, Solomon; Meso, Peter
ABSTRACT: In almost all low-income countries, small- and medium-sized enterprises (SMEs) are a primary engine for the country's economic development. While many information and communications technology (ICT) diffusion studies exist, only few focus on low-income countries and even fewer employ Bass-based analysis to examine ICT diffusion in these countries. This study applies the Bass diffusion model to understand SME adoption of ICT in Cameroon, a low-income country. The Bass model was employed because of its predictive capacity. We find that diffusion of ICT among SMEs in the context of a low-income economy is largely driven by forces of imitation rather than forces of innovation. Contributing to practice, this study finds that SMEs with greater sizes, multiple plants, and whose owners have higher education have a greater tendency to adopt ICT early. The theoretical contribution of the paper is applying the well-recognized Bass model from marketing to the IT/IS field and applying it within a low-income country environment by evaluating diffusion of ICTs among SMEs in Cameroon.